2021
DOI: 10.1111/jog.14816
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategy for locally advanced squamous cell cervical cancer with clinically positive pelvic lymph nodes metastasis

Abstract: Aim To determine the optimal treatment for locally advanced squamous cell cervical cancer with clinical positive pelvic lymph nodes metastasis (cN1). Methods We enrolled patients with squamous cell cervical cancer with 2008 FIGO stages IB, IIA, or IIB diagnosed with cN1, who were treated at Hyogo Cancer Center between April 2010 and December 2016. Patients with para‐aortic lymph nodes metastasis were excluded. Results Of the 69 eligible patients, 24 underwent concurrent chemoradiotherapy (CCRT), 11 underwent r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…NACT plus surgery, which could reduce LNM and even achieve longer 5-year DFS and OS, may represent a new therapeutic option for stage IIIC cervical cancer. 37 , 38 A systematic review and meta-analysis showed that in stages IB1 to IIB, preoperative NACT plus radical surgery resulted in a 23% probability of LNM, which was lower than those receiving radical surgery only. In stages IIA and IIB, the effect of NACT on reducing LNM was more obvious.…”
Section: Resultsmentioning
confidence: 99%
“…NACT plus surgery, which could reduce LNM and even achieve longer 5-year DFS and OS, may represent a new therapeutic option for stage IIIC cervical cancer. 37 , 38 A systematic review and meta-analysis showed that in stages IB1 to IIB, preoperative NACT plus radical surgery resulted in a 23% probability of LNM, which was lower than those receiving radical surgery only. In stages IIA and IIB, the effect of NACT on reducing LNM was more obvious.…”
Section: Resultsmentioning
confidence: 99%
“…There was some studies on this issue.Lijie Cao et al [12]conducted a retrospective study involving 861 cases of cervical squamous cell carcinoma with lymph node metastasis,with 85 patients received no adjuvant treatment, 283 patients treated with radiotherapy, and 493 patients with concurrent chemoradiotherapy(CCRT).They concluded that adjuvant radiotherapy or CCRT was not associated with a survival bene t compared to surgery with no adjuvant treatment. Some studies, however, had a different view.Takashi Shibutani et al [13] conducted a study involving 69 squamous cell cervical cancer with lymph node metastases.They recommend avoiding RH as primary treatment for those patients and CCRT should be considered.A single-center, retrospective study conducted by Jongmoo Park et al [14]reached similar conclusions.For cervical cancer patients with pelvic lymph node metastases, more studies focused on the treatment of postoperative adjuvant therapy,because these studies were conducted before the FIGO 2018 staging system was published. At present, the treatment strategies for patients with FIGO 2018 stage IIIC1 cervical cancer are inconclusive and few studies have been conducted, and there is no discussion on adenocarcinoma.In 2021, Shuko Miyahara et al [15] conducted a study of 92 patients with stage IIB-IVA cervical cancer who received radical radiotherapy.…”
Section: Data Ltering Processmentioning
confidence: 99%